The role of selection in the comprehension of focus alternatives - Husband, M; Ferreira, F (Routledge, 2015)
Successful language comprehension often requires comprehenders to infer contrastive focus alternatives, but the mechanisms used to establish contrastive alternatives are still poorly understood. We propose that comprehenders establish contrastive alternatives by using selection mechanisms that distinguish contrastive from non-contrastive candidates. To examine this proposal, we investigated the time course of contrastive alternatives in two cross-modal priming experiments, manipulating contrastive focus on prime words and the contrastiveness of visual targets. Experiment 1 examined early processing where comprehenders are entertaining candidates for contrastive alternatives. Experiment 2 examined later processing where comprehenders have selected contrastive alternatives from the candidate set. Results demonstrated that when primes were contrastively focused, initially both contrastive and non-contrastive associates were facilitated, but, in subsequent processing, non-contrastive associates became deactivated while contrastive associates maintained facilitation. We argue that selection mechanisms distinguish contrastive from non-contrastive candidates by deactivating non-contrastive candidates, enabling comprehenders to draw proper inferences about speakers’ implicit meanings.